A Case Study Investigation of Special Needs Inclusion Policy Implementation in three Abu Dhabi Primary Schools In the UAE - NFOR, JACQUI LOTTIN (2017)
In the UAE, education has been identified as top priority and the government has taken steps to promote inclusive education to protect the rights of persons with disability, using Law No 29 of 2006, pertaining to the ‘‘Rights of Persons with Special Needs’’ (Ministry of Social Affairs 2006). Based on this law, all young people are afforded equal rights and opportunities (Farouk 2008), which aligns with UNESCO’s Salamanca Convention Framework for Action Statement (1994) to accommodate all children in mainstream schools, regardless of their physical, intellectual, social, or emotional condition. This government policy was to fit in with the proponents of inclusive education which refers to all students, who ‘’irrespective of their strengths or weaknesses, will become part of the school community’’ (Hassan 2008, p.8). This research study adopts a qualitative approach that investigates the implementation of Abu Dhabi Education Council’s (ADEC) special educational needs policy, with inclusion as the guiding platform for this policy. Employing a collective case study investigation, the study evaluates school and HQ staff applying their comprehension of the intricate idea of inclusive practices in school settings. This provides a rich and contextualized view of how these various stakeholders, including mainstream teachers, special needs teachers, principals, and students, perceive its implementation. Research instruments to compile the data for triangulation (Stake 1995; Denzin 1984, 1989), employs qualitative methods that include observations, semi-structured interviews, as well as documentation analysis. The research guiding question is: ‘To what extent is Abu Dhabi Education Council’s Special Educational Needs Policy implemented in practice and what can be done to improve its implementation to support inclusive education in government primary schools in Abu Dhabi ’. In order to effectively answer this question, this research focuses on four areas to evaluate policy impact, namely the curriculum, accessibility, assessment and in-service teacher professional development. These four key areas gives some weight to the study. The investigation targets the culture within five primary schools with reference to their inclusive policies and practices. Also central to the study analysis is employing The Index for Inclusion which is a tool with a set of indicators developed by Booth & Ainscow (2011) to measure the above four areas. Analysis from the themes which emanated from this study reveals that, Abu Dhabi Education Council’s Special Educational Needs Policy is robust, with many positive characteristics that align with similar effective global education policies that support an inclusive learning culture across schools. However, there are still gaps between policy implementation and practice within schools, ranging from a lack of understanding of what the policy entails to effective knowledge of special educational needs practices, as well as continuing professional development. Furthermore, additional research is still needed to gather reliable data to support policy implementation as required by Federal Law on an inclusive educational system, not just within Abu Dhabi Education Council schools, but across schools in the UAE. Insights into the contexts are used to put forward research- based recommendations for future practice which will improve the effectiveness in implementing inclusive practices.